Amnesty International calls for human rights bodies to investigate killings of civilians by the Ethiopian National Defense Forces (ENDF) in Merawi town, on 29 January, as war crimes of murder and extrajudicial executions - Amnesty International (Amnesty International, 2024)
Claims by the Ethiopian government that accountability has already been achieved for crimes committed in the war in northern Ethiopia demonstrate lack of political commitment to genuine justice and accountability.

Mass death, torture and other violations against people detained in aftermath of Islamic State defeat – new report - Amnesty International (Amnesty International, 2024)
People detained following the territorial defeat of the Islamic State (IS) armed group are facing systematic violations and dying in large numbers due to inhumane conditions in north-east Syria, Amnesty International said in a new report.

Resettlement as a Human Rights Issue: Submission to the UN Special Rapporteur on the Right to Adequate Housing - Amnesty International (Amnesty International, 2024)
Amnesty International welcomes the call for inputs by the UN Special Rapporteur on Adequate Housing as a Component of the Right to an Adequate Standard of Living, and on the Right to Non-discrimination in this Context, to inform his report to the General Assembly in October 2024, and for developing international guiding principles for resettlement.

Amnesty International launches book ‘Images of Rebellion’, a testament to civil resistance - Amnesty International (Amnesty International, 2024)
Amnesty International has published the book Images of Rebellion, an extraordinary visual compilation that chronicles and celebrates the defiant spirit of civil resistance in Cuba. The book contains a poignant selection of the more than 21,000 letters and drawings sent to Luis Manuel Otero Alcántara, Cuban artist and prisoner of conscience, in a global outpouring of support.

New short film highlights devastating impact less-lethal weapons are having on protesters globally - Amnesty International (Amnesty International, 2024)
Amnesty International is launching a powerful film showing the devastating impact less-lethal weapons are having on protesters globally, with many suffering life-long injuries and permanent disabilities. The new film, which features Leidy Cadena who was blinded by police in 2021 during a protest which was part of the National Strikes in Colombia, shows the devastating impact such weapons can have.